2017
DOI: 10.5039/agraria.v12i1a5410
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and phosphate fertilization on star fruit tree seedlings

Abstract: The success of star fruit cultivation deployment begins with the use of good quality seedlings Thus the inoculation of mycorrhizal fungi in culture seedling can be an alternative, since it was found success in both growth as nutritional aspect fruit species. In this sense, the aim of this study was to evaluate the effects of arbuscular mycorrhizal fungi (AMFs) on growth and mineral composition of star fruit seedlings, cultivated under different doses of phosphorus (P). The experiment was conducted in a greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The fertilization of star fruit seedlings, as well as of other fruit trees, is performed in an imprecise or empirical way, with lack of research in this regard . Evaluating phosphate fertilization in 120-day-old star fruit seedlings grown in soil, Vitorazi Filho et al (2017) observed that the maximum growth was obtained with doses of 143.8 mg kg -1 of P and for the basic fertilization of seedling growth, 20 mg kg -1 of N and 120 mg kg -1 of KCl were applied.…”
Section: Seedling Fertilization and Nutritionmentioning
confidence: 99%
“…The fertilization of star fruit seedlings, as well as of other fruit trees, is performed in an imprecise or empirical way, with lack of research in this regard . Evaluating phosphate fertilization in 120-day-old star fruit seedlings grown in soil, Vitorazi Filho et al (2017) observed that the maximum growth was obtained with doses of 143.8 mg kg -1 of P and for the basic fertilization of seedling growth, 20 mg kg -1 of N and 120 mg kg -1 of KCl were applied.…”
Section: Seedling Fertilization and Nutritionmentioning
confidence: 99%